Integrating Sleep Quality, Cardiac Autonomic Function, Cognitive Processing Speed, and Academic Performance Assessment in Undergraduate Medical Students: A Pilot Study - ZULQERNAIN, ALI; SYED, ZOHAIB; FAROOQ, RAI KHALID (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Poor sleep quality is common among medical students and has been associated with impaired learning, attention, and academic performance. Heart rate variability (HRV) provides a non-invasive measure of cardiac vagal modulation and may help explain the physiological pathway linking sleep and learning. Before a larger prospective study, protocol feasibility needed to be tested in a small student cohort. Objectives: This pilot study evaluated the feasibility and acceptability of assessing sleep quality, cardiac autonomic function, reaction time, and examination performance in undergraduate medical students. A secondary objective was to estimate preliminary effect sizes for planning a larger study. Methods: A single-center pilot observational study was conducted among 30 second-year medical students. Sleep quality was assessed using the Pittsburgh Sleep Quality Index. Resting heart rate, blood pressure, and 5-minute heart rate variability were recorded under standardized morning conditions. Root mean square of successive differences between normal heartbeats (RMSSD) was selected as the primary HRV index. Reaction time was assessed using an attention task. Academic performance was measured using a summative academic examination. Feasibility outcomes included recruitment rate, retention rate, data completeness, HRV recording success, participant acceptability, and achievement of predefined progression criteria. Results: Twenty-eight students underwent the entire processes of study. In 29 out of 30 sessions, completeness of data was 96.4 and technical acceptable HRV recordings were accomplished. There were all the predetermined progression criteria that were met. Control: There were sixteen poor and fourteen good sleepers. Sleep deprived individuals were less RMSSD, with a high resting heart rate, slower reaction time, and lower grades on academic tests. RMSSD, reaction time, and examination performance had large preliminary effect sizes. There was a negative correlation between sleep quality measured by Pittsburgh Sleep Quality Index (PSQI) score and RMSSD and examination score. Conclusion: The protocol was viable, acceptable and fit to be extended to a larger prospective study. Early evidence indicates that sleep quality could be linked with worse vagal modulation and slower cognitive processing, and worse performance in physiology exams amongst medical students.